Validation Study of the Child and Youth Resilience Measure (CYRM-28) Among Dutch Youth - Jonkman, Harrie; Rooijen, Maaike van; Wiersma, Marte; Goor, Roel van (Frontiers in Psychiatry, 2022)
A validation study of a 28-item Child and Youth Resilience Measure (CYRM-28) among a Dutch sample was presented. A sample of 525 adolescents (16–20 years old) from the CYRM-28 in the Netherlands was analyzed. Descriptive statistics, confirmatory factor analysis (CFA), construct validity analysis, and reliability tests were carried out on data collected to identify and present factor structure, construct validity, and reliability. The CFA suggested a three-structure framework with individual, relational, and contextual subscales. Overall, the results were similar to the results found in other international validation studies measuring resilience among teenagers. Integral support of vulnerable youth needs to fit in with the lives and world of these adolescents in their transition to adulthood. Measuring resilience with the CYRM-28 can be used to assist this. Dutch individual and contextual subscales need further research.